RANCANGAN MASALAH MATEMATIKA UNTUK MENGIDENTIFIKASI BERPIKIR GEOMETRIS SISWA - Noor Fajriah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Geometric thinking has a very important role in developing students' mathematical thinking. To find out geometric thinking students needed a problem that could identify geometric thinking. The problem must be in accordance with the objectives to be measured, to meet validity and reliability as a valuation tool. The purpose of this research was to obtain the design of geometry problems to be able to identify valid and reliable geometric thinking. The descriptive method was used in this research. There are 6 people as validators and 3 junior high school students for testing. The results obtained prototype problems designed to pay attention to aspects of the material in accordance with the level of junior high school students and bring visualization, construction and reasoning activities. The construction aspect in which the problem does not lead to multiple interpretations. is clear and uses a question word/ command whose completion is a description. Aspects of language where the language is communicative easily understood and in accordance with the rules of the Indonesian language is good and true and meets the criteria of legibility.